Stress appraisals influence athletic performance and psychophysiological response during 16.1 km cycling time trials - Thompson, M. A.; Toner, J.; Perry, J. L.; Burke, R.; Nicholls, A. R. (Psychology of Sport and Exercise, 2020)
Objectives: We examined how stress appraisals were associated with emotions, coping behaviours, as well as subjective and objective measures of performance.